2015
DOI: 10.2147/ijn.s76742
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based synergistic dual-drug codelivery system for enhanced apoptosis of tumor cells

Abstract: A microemulsion-based synergistic dual-drug codelivery system was developed for enhanced cell apoptosis by transporting coix seed oil and etoposide into A549 (human lung carcinoma) cells simultaneously. Results obtained by dynamic light scattering showed that an etoposide (VP16)-loaded coix seed oil microemulsion (EC-ME) delivery system had a small size around 35 nm, a narrow polydispersity index, and a slightly negative surface charge. The encapsulating efficiency and total drug loading rate were 97.01% and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Celastrol, STS, HAuCl 4 , NaBH 4 , vitamin C, and hexadecyl trimethyl ammonium bromide (CTAB) were bought from Sinopharm Group Co., Ltd. (Shanghai, China). Coix oil was prepared by our group using previously reported methods . Kolliphor RH40, PEG400, and cholesterol were purchased from Sigma-Aldrich Co., Ltd. (MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Celastrol, STS, HAuCl 4 , NaBH 4 , vitamin C, and hexadecyl trimethyl ammonium bromide (CTAB) were bought from Sinopharm Group Co., Ltd. (Shanghai, China). Coix oil was prepared by our group using previously reported methods . Kolliphor RH40, PEG400, and cholesterol were purchased from Sigma-Aldrich Co., Ltd. (MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the preparation technology of ECG-MEs had been reported as a ‘one-step emulsion’ method (Qu et al., 2015 , 2017 ). Hereon, we plotted pseudoternary phase diagram to further investigate the influence of weight ratio between G-Rh2, RH40 and PEG400 on the formation of microemulsion.…”
Section: Methodsmentioning
confidence: 99%
“…Schizandrin A–docetaxel-loaded microemulsion (SD-ME) was synthesized by single emulsion method as described by previous publication (Qu et al, 2015 ). First, 5 mg of DTX and 5 mg of schizandrin A were simultaneously dissolved in 200 mg of Labrafil M CS1944 with a strong stirring at 600 rpm using an MYP11-2 homoiothermal magnetic stirrer (MeiYingPu instruments Co., Ltd., Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…By right of outstanding integration of multicomponent, ME is an appropriate vehicle for the co-delivery of various types of functional agents, resulting in the integration of the respective advantages. For instance, Qu and coworkers developed an ME-based co-delivery system carrying coix seed oil, etoposide, and coix seed polysaccharide, which enhanced apoptosis of tumor cells and improved tumor-specific targeting (Qu et al, 2015 , 2016 ). Similarly, incorporation of an anticancer drug and a P-gp inhibitor into a microemulsion system can potentially overcome the MDR in esophageal carcinoma.…”
Section: Introductionmentioning
confidence: 99%